2017
DOI: 10.3389/fpsyg.2017.00300
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Functional Flexibility in Infant Vocalizations of the First 3 Months

Abstract: Functional flexibility, as manifest in the use of any word or sentence to express different affective valences on different occasions, is required in linguistic communication and can be said to be an infrastructural property of language. Early infant vocalizations (protophones), believed to be precursors to speech, occur in the first month and are functionally different from non-speech-like signals (e.g., cries and laughs). Oller et al. (2013) showed that infants by 3 months used three different protophone typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
1
33
2
Order By: Relevance
“…Another example: a fussy protophone, not directed toward anyone, can be treated as having the illocutionary force of complaint. Pre-linguistic infants express varying illocutionary forces and varying emotional content (i.e., positive, neutral, and negative) in early protophones beginning at birth [53,65] (see Appendix D of S1 Data). This fact indicates that infants have the capacity to produce a single protophone type with different illocutionary forces on different occasions, indicating they possess a vocal capability that is, of course, required of all words and sentences in mature language.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Another example: a fussy protophone, not directed toward anyone, can be treated as having the illocutionary force of complaint. Pre-linguistic infants express varying illocutionary forces and varying emotional content (i.e., positive, neutral, and negative) in early protophones beginning at birth [53,65] (see Appendix D of S1 Data). This fact indicates that infants have the capacity to produce a single protophone type with different illocutionary forces on different occasions, indicating they possess a vocal capability that is, of course, required of all words and sentences in mature language.…”
Section: Plos Onementioning
confidence: 99%
“…A fundamental question that requires answering based on the present work is: If protophones are not directed to caregivers, what is their purpose from a developmental or an evolutionary standpoint? What advantage could be associated with producing vocal sounds that are largely affectively neutral, produced most commonly in apparent comfort, but without social directivity [53,65]?…”
Section: Plos Onementioning
confidence: 99%
“…Our research suggests that in the evolution of human language, a key foundational divergence from the primate background may have involved an increasing tendency in the hominin line to vocalize freely, not in the form of language, but in exploratory vocalization with flexible vocal expression of emotional states (Oller, 2000; Oller and Griebel, 2008). In part, this line of reasoning is inspired by the fact that human infants begin life already producing copious exploratory and functionally flexible vocalization (Stark et al, 1975; Koopmans-van Beinum and van der Stelt, 1986; Nathani et al, 2006; Oller et al, 2013; Jhang and Oller, 2017). Such sounds are not language, but the ability and the inclination to produce them flexibly and extensively form crucial foundations for language (Oller, 1981; Koopmans-van Beinum and van der Stelt, 1986; Locke, 1993; Griebel and Oller, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the first half year of life, protophones such as vowel-like sounds (hereafter “vocants”), squeals, growls, and raspberries, without the well-formed consonant-vowel-like components of canonical babbling, have been argued to form foundations for all subsequent vocal development necessary for language, including canonical babbling ( Oller, 1980; Koopmans-van Beinum and van der Stelt, 1986). These early protophone sounds, like canonical babbling, are typically produced exploratorily and can accompany the full range of positive to neutral to negative affect as reflected in facial expression (Oller et al, 2013; Jhang and Oller, 2017), and although they usually occur at low or moderate arousal, they can also accompany intense emotion and high arousal. It is a requirement of language that all words or sentences be producible at will, at any point that a speaker chooses to produce them, regardless of emotional state or external circumstance.…”
Section: Introductionmentioning
confidence: 99%
“… 3 More recent work from our group showed that flexible relations of protophones with neutral and negative facial affect also occurred in infants from 0 to 3 months of age (positive facial expressions were rare in these very young infants) ( Jhang and Oller, 2017 ). …”
mentioning
confidence: 98%